Evaluation of Chamois Leather Using Corn Oil (Zea Mays) as The Tanning Material - wehandaka - pancapalaga; Suyatno Suyatno; Hysam Jamaluddin (Buletin Peternakan, 2021)
One of the main characteristics of chamois leather is its high ability to absorb water; thus, chamois leather is generally used for cleaning and drying. The usual tanning material for chamois leather is fish oil. However, it makes the chamois leather product have a strong odor. This study aims to evaluate the quality of chamois leather from rabbit skin tanned with corn oil. The treatments included the addition of several corn oil concentrations consisting of P0 (30 % fish oil), P1 (10 % corn oil), P2 (20% corn oil), and P3 (30% corn oil). The results showed that corn oil as a tanning material was able to increase the ash content, elongation, tear strength, and water absorption of chamois skin and was able to reduce oil content, and did not change the tensile strength, color and odor of the chamois leather produced. The quality of chamois leather with 30% corn oil indicated the ash content as much as 3.19%, oil content as much as 7.87%, elongation as much as 94.51%, tear strength as much as 46.47 N/mm, water absorption (24 hours) as much as 279.03%; and tensile strength as much as 9.9 N/mm2. It also produced yellowish-white color with no odor. This quality has met the requirements of the Indonesian National Standard (SNI): 0617521990. The study concludes that 30% corn oil can substitute fish oil to produce chamois leather.